USE OF INNOVATIVE METHODS IN IMPROVING THE QUALITY OF EDUCATION IN PHYSICAL EDUCATION CLASSES: USE OF INNOVATIVE METHODS IN IMPROVING THE QUALITY OF EDUCATION IN PHYSICAL EDUCATION CLASSES - to'ychiyev, sobir (Физическое воспитание, спорт и здоровье, 2025)
The teacher sets goals for the lesson, makes decisions, plans, organizes the lesson process, monitors its progress and results, and changes the content as needed.